Geocronologia e petrografia do ortognaisse São Sebastião do Paraíso, sudeste de Goiás - Santos, Pedro Henrique dos [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Idades isotópicas de cristais de zircão (U/Pb por LA-ICP-MS - Laser Ablation Inductively Coupled Plasma Mass Spectrometry) e Sm/Nd (rocha total) foram determinadas em amostra do ortognaisse São Sebastião do Paraíso que ocorre a NW da cidade de Caldas Novas (Goiás), na Zona Interna da Faixa Brasília, intercalado em metassedimentos do Grupo Araxá. Grãos de zircão analisados mostram uma idade discordante de 2.140,28±7,83 Ma, que é assumida como a idade de cristalização do protólito ígneo do ortognaisse. A idade modelo TDM(Nd) de 2.203,4 Ga e o valor εNd(t), para idade de cristalização de 2.140,28, positivo (2,43), sugere que este ortognaisse trata-se de uma rocha formada em um evento magmático juvenil paleoproterozoico, sendo possivelmente um correspondente do embasamento paleoproterozoico da Faixa Brasília.

Isotopic ages of zircon crystals (U/Pb by LA-ICP-MS - Laser Ablation Inductively Coupled Plasma Mass Spectrometry) and Sm/Nd (total rock) were determined in a sample of the São Sebastião do Paraíso orthogneiss located NW of the city of Caldas Novas (Goiás), in the Internal Zone of the Brasília Belt, interspersed with metasediments of the Araxá Group. Analyzed zircon grains show a discordant age of 2140.28±7.83 Ma, which is assumed to be the age of crystallization of the igneous protolith of the orthogneiss. The TDM(Nd) model age of 2,203.4 Ga and the εNd(t) value for crystallization age of 2,140.28, positive (2.43), suggest that this orthogneiss is a rock formed in an event Paleoproterozoic juvenile magmatic, possibly being a correspondent of the Paleoproterozoic basement of the Brasilia Belt.
Geochronology and petrography of the orthogneiss São Sebastião do Paraíso, southeastern Goiás
Keywords: Geologia; Faixa Brasília; Grupo Araxá; Geocronologia U/Pb e Sm/Nd; Petrografia; Geology; Brasília belt; Araxá group; U/Pb and Sm/Nd Geochronology; Petrography; Ortognaisse São Sebastião do Paraíso; Orthogneisse São Sebastião do Paraíso